Pengembangan Mode Offline dan Sinkronisasi Data pada Aplikasi Absensi Berbasis QR Code untuk Karyawan PT.Bintang Energi Pratama - Nadya Kusuma Indah; Lidya Wati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study proposes the development of a QR Code-based attendance application equipped with offline mode and data synchronization features, using the Rapid Application Development (RAD) method. In PT.Bintang Energi Pratama, employee attendance management is a significant challenge, especially when the internet connection is unstable. Therefore, this system is designed to enable efficient attendance recording even without internet access, with data stored locally. When the connection is back available, the system automatically synchronizes data to the central server, ensuring the accuracy and integrity of attendance information. The Rapid Application Development (RAD) method is used in the development of this system to accelerate the design, implementation, and testing processes, and ensure that the required features can be quickly adapted based on user feedback. The results of this study are expected to improve the productivity and efficiency of employee attendance management, as well as provide an effective solution to the challenges of attendance in a dynamic work environment.